CEMARAN PESTISIDA KLOR-ORGANIK PADA SEDIMEN DANAU BUYAN BULELENG BALI - Putra Manuaba, Ida Bagus (Bumi Lestari, 2012)
This is an expost facto study with Analytical Cross Sectional Study design, within two step activities, i.e. field study in order to gain sampling zone and obtaining sample needed. Followed by laboratory works in order to obtain pesticide residual contamination on water. Sample preparation for this purposed was carried out following a standard method. Gas chromatography was employed in order to gain the pesticide contaminant. Positive organochlorine pesticide contaminant, i.e. DDT and chlorotalonile were observed from 55 sampling point of sediment taken from 5 sampling zone. DDT in the sediment is 13.6 ppb with still bellow the maximum level of 42 ppb. Chlorotalonile in sediment is 12.3 ppb. There is no threshold value of chlorotalonile, however, this contamination still bellow the RfD 15 ppb and ADI 30 ppb (PIP, 1995; Caroline, 1997).
Keywords: organochlorine pesticide, residual contaminant, expost facto